2019
DOI: 10.2174/1386207322666190119162352
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Toxicity of Addition of Bevacizumab to Chemotherapy in Patients with Metastatic Colorectal Cancer

Abstract: Background: Pre-treated patients with first-line treatment can be offered a second treatment with the aim of improving their poor clinical prognosis. The therapy of metastatic colorectal cancer (CRC) patients who did not respond to first-line therapy has limited treatment options. Recently, many studies have paid much attention to the efficacy of bevacizumab as an adjuvant treatment for metastatic colorectal cancer. Objectives: We aimed to evaluate the efficacy and toxicity of bevacizumab plus chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
3
1
0
Order By: Relevance
“…Our results also showed that patients with unresectable CLLMs would benefit from systemic therapy first mode rather than primary lesion resected mode in the overall survival, which is consistent with previous reports 36. The addition of targeted agents, like cetuximab and bevacizumab, has been reported to be associated with a favorable PFS and OS in the previous studies 3,22. And, it is also worth noting that local treatments, like TACE, are associated with poorly controlled progression of CLLMs and shorter PFS in our study, because local treatment was always used when the shrinkage of tumors was not apparent 23,29…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results also showed that patients with unresectable CLLMs would benefit from systemic therapy first mode rather than primary lesion resected mode in the overall survival, which is consistent with previous reports 36. The addition of targeted agents, like cetuximab and bevacizumab, has been reported to be associated with a favorable PFS and OS in the previous studies 3,22. And, it is also worth noting that local treatments, like TACE, are associated with poorly controlled progression of CLLMs and shorter PFS in our study, because local treatment was always used when the shrinkage of tumors was not apparent 23,29…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we identify targeted therapy as another independent predictor in multivariate analysis. This was similar to previous studies, in which adding cetuximab or bevacizumab to chemotherapy was associated with facilitated radical resections of CLLMs 3,22. And TACE was also identified as another independent predictor in multivariate analysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…At the molecular level, VEGF and its receptor (VEGFR) play major roles in the angiogenesis that characterizes advanced cancer. Several authors have reported significant improvements in progression-free survival (PFS), overall survival (OS) and response rate (RR) in mCRC patients treated with CT + BVZ compared to CT alone [7][8][9][10][11][12]. However, not all patients respond in the same way to treatment probably through the development of treatment resistance mechanisms involving activation of proangiogenic pathways or tumour recruitment of cells that produce proangiogenic factors, recruitment of hematopoietic cells and inflammatory cells into the tumour, and heterogeneity of genetically unstable tumour cells [13,14].…”
Section: Introductionmentioning
confidence: 99%